IL4-10 fusion protein has chondroprotective, anti-inflammatory and potentially analgesic effects in the treatment of osteoarthritis. Issue 8 (August 2018) - Steen-Louws, C.; Popov-Celeketic, J.; Mastbergen, S.C.; Coeleveld, K.; Hack, C.E.; Eijkelkamp, N.; Tryfonidou, M.; Spruijt, S.; van Roon, J.A.G.; Lafeber, F.P.J.G.
Summary: Objective: Effective disease-modifying drugs for osteoarthritis (DMOAD) should preferably have chondroprotective, anti-inflammatory, and analgesic activity combined in a single molecule. We developed a fusion protein of IL4 and IL10 (IL4-10 FP), in which the biological activity of both cytokines is preserved. The present study evaluates the chondroprotective, anti-inflammatory, and analgesic activity of IL4-10 FP in in vitro and in vivo models of osteoarthritis. Methods: Human osteoarthritic cartilage tissue and synovial tissue were cultured with IL4-10 FP. Cartilage proteoglycan turnover and release of pro-inflammatory, catabolic, and pain mediators by cartilage and synovial tissue were measured. The analgesic effect of intra-articularly injected IL4-10 FP was evaluated in a canine model of osteoarthritis by force-plate analysis. Results: IL4-10 FP increased synthesis ( P = 0.018) and decreased release ( P = 0.018) of proteoglycans by osteoarthritic cartilage. Release of pro-inflammatory IL6 and IL8 by cartilage and synovial tissue was reduced in the presence of IL4-10 FP (all P < 0.05). The release of MMP3 by osteoarthritic cartilage and synovial tissue was decreased ( P = 0.018 and 0.028) whereas TIMP1 production was not significantly changed. Furthermore, IL4-10 FP protected cartilage against destructive properties of synovial tissue mediators shown by the increased cartilage proteoglycan synthesis ( P = 0.0235) and reduced proteoglycan release ( P = 0.0163). Finally, intra-articular injection of IL4-10 FP improved the deficient joint loading in dogs with experimentally induced osteoarthritis. Conclusion: The results of current preliminary study suggest that IL4-10 FP has DMOAD potentials since it shows chondroprotective and anti-inflammatory effects in vitro, as well as potentially analgesic effect in a canine in vivo model of osteoarthritis.